Seawater products for nasal lavages. Comparison and literature review: Productos de agua de mar para lavados nasales. Comparación y revisión bibliográfica - López Barea, Irene (2023)
Introduction. There is a wide range of seawater products for nasal lavages. Their efficacy and superiority over conventional saline solutions are not well established. Objectives. To analyse the best-selling seawater products, as well as reviewing the most recent literature regarding nasal lavages. Methods. Comparative study of composition, administration mode, age indicated for its use, price and bibliography provided on the web of the seawater products usually available in pharmacies. Analysis of the bibliography provided and review of the scientific evidence regarding nasal lavages with saline solutions or seawater. Results. 44 products from 11 manufacturers were analysed. The concentration of sodium chloride varies from 0.9% to 2.5%. The most frequent mode of application is spray. The addition of plants, salts and other components is common. Only two brands provide bibliographic references on their website. According to the literature reviewed, both saline solutions and seawater seem especially useful in the treatment of upper respiratory tract infections and allergic rhinitis. Conclusions. There is no solid scientific evidence regarding the benefits of nasal lavages. With the current evidence it is not possible to recommend seawater over conventional saline or to establish the optimal concentration of the solution or the most convenient mode of administration. The addition of elements to seawater solutions is not justified enough.